Analysis of Treatment Period for TB Patients Using The Kaplan-Meier Method - Andini, Kiki Andini; Marsanda, Mareta; Wahyuni, Olivia Nindi; Prabowo, Agung (Operations Research: International Conference Series, 2025)
This study aims to analyze the duration of treatment for tuberculosis (TB) patients using the Kaplan-Meier method, a non-parametric approach in survival analysis. The research data comes from the Banyumas Regency Health Office for the period March 2023 to November 2023, with a total of 25 patients. The variables analyzed include gender, age, and treatment completion status. The results of the study showed that the chance of incomplete treatment was higher in male patients than in female patients, and the chance of incomplete treatment in patients aged >40 years was higher than in the age group ≤40. The Kaplan-Meier method was used to calculate the survival function, hazard function, and survival time distribution, which provides an in-depth understanding of the dynamics of TB treatment. These findings can assist policymakers in improving the effectiveness of TB treatment in Banyumas Regency.